PERCEPTION DIMENSIONS OF THE USE OF ELECTRONIC PARKING IN TRADITIONAL MARKETS AS AN EFFORT TO INCREASE REGIONAL ORIGINAL INCOME - Ani; Rochmat Aldy Purnomo; Yeni Cahyono; Asis Riat Winarno; Choirul Hamidah (Universitas Tidar, 2024)
Electronic parking is one of the public service innovations that has the potential to increase local revenue in Ponorogo Regency. This innovation takes the form of an application that regulates parking in market areas that tend to be congested by utilizing technology such as parking sensors and applications, drivers can easily find available parking spaces and make payments electronically and also manually. The phenomenon in market parking management research is that it is not yet optimal in terms of service to the community and maximizing regional income from the market parking levy sector. This research aims to examine the dimensions of public perception regarding the use of market electronic parking as a strategy to increase Regional Original Income and evaluate user perceptions of the trust and economic benefits of electronic parking at Tonatan Market, Ponorogo. This research uses a method with a qualitative approach. The data collection technique uses an interactive approach using triangulation techniques such as observation, interviews, questionnaires and document retrieval. Samples were taken from Tonathan market parking users totaling seven informants. The research results show that there are people who support and do not support electronic parking innovation. The Department of Trade, Cooperatives and Micro Enterprises of Ponorogo Regency also supports the innovation of electronic parking because it can increase regional income.